RETRACTED: Mixed convective heat transfer in a power-law fluid in a square enclosure: Higher order finite element solutions - Bilal, S.; Khan, Noor Zeb; Fatima, Iqra; Riaz, Arshad; Ansari, Ghulam Jillani; Alhazmi, Sharifah E.; El-Din, ElSayed M. Tag (Frontiers in Physics, 2023)
Incorporation of momentum gradients produced due to inertial motion of lid along with the presence of temperature differences in configuration make the physical problem more significant. The joint variation of momentum and thermal diffusions in diversified nature liquids is recognized as mixed convection. A valuable attention has been received by such phenomenon in different areas of science and technology like in, wind current based solar receivers, electronic instruments, control of emergency shut down in reactors, thermal exchangers, oceanic currents, control of atmospheric pollution and so on. So, the prime focus is to contemplate hydrothermal characteristic of power law fluid contained in a square cavity with movement of upper lid and thermally adiabatic. Rest of extremities are taken to at rest and base wall is prescribe with uniform/non-uniform temperature distributions. Governing formulation of problem is handled by executing finite element approach. Hybrid meshing is performed for domain discretization and weak variational formulation is utilized for formulation discretization. Second degree polynomials are employed as interpolation function and providing information about velocity and temperature distributions at boundary and intermediate nodes. System of finalized non-linear equations are resolved by software known as PARADISO. Results for velocity and temperature distributions are attained comparatively for uniformly and non-uniformly heated profiles. Kinetic energy and average Nusselt number are also computed against flow concerning variables. From the attained graphical and tabular data, it is deduced that by increasing Reynold number, inertial forces dominate over buoyancy forces and effect of lid movement is prominent on flow characteristics. It is also inferred that for shear thickening case and for all values of Reynold number, the average Nusselt number shows constant behavior.